Targeting tyrosine-kinases and estrogen receptor abrogates resistance to endocrine therapy in breast cancer - Liu, Shuying (Oncotarget, 2014)
Despite numerous therapies that effectively inhibit estrogen signaling in breast cancer, a significant proportion of patients with estrogen receptor (ER)-positive malignancy will succumb to their disease. Herein we demonstrate that long-term estrogen deprivation (LTED) therapy among ER-positive breast cancer cells results in the adaptive increase in ER expression and subsequent activation of multiple tyrosine kinases. Combination therapy with the ER down-regulator fulvestrant and dasatinib, a broad kinase inhibitor, exhibits synergistic activity against LTED cells, by reduction of cell proliferation, cell survival, cell invasion and mammary acinar formation. Screening kinase phosphorylation using protein arrays and functional proteomic analysis demonstrates that the combination of fulvestrant and dasatinib inhibits multiple tyrosine kinases and cancer-related pathways that are constitutively activated in LTED cells. Because LTED cells display increased insulin receptor (InsR)/insulin-like growth factor 1 receptor (IGF-1R) signaling, we added an ant-IGF-1 antibody to the combination with fulvestrant and dasatinib in an effort to further increase the inhibition. However, adding MK0646 only modestly increased the inhibition of cell growth in monolayer culture, but neither suppressed acinar formation nor inhibited cell migration in vitro and invasion in vivo. Therefore, combinations of fulvestrant and dasatinib, but not MK0646, may benefit patients with tyrosine-kinase-activated, endocrine therapy-resistant breast cancer.